The Synergy of School and Parental Roles in Preventing Addictive Substance Abuse: A Case Study of State Elementary School 56 in Bengkulu City - Rintan Dwi Utami; Panji Suminar; Diyas Widiyarti (The Innovation of Social Studies Journal, 2026)
Addictive substance abuse among elementary school students is a critical issue requiring collaborative solutions from schools and families. This study aims to explore the patterns and mechanisms of synergy between schools and parents in efforts to prevent addictive substance abuse at SD Negeri 56 (State Elementary School 56) in Bengkulu City. This study employed a qualitative case study design. Data collection was conducted through in-depth interviews, participant observation, and document analysis involving eleven informants, consisting of the principal, teachers, parents, and students. The findings reveal the formation of a bottom-up, tiered synergy, where the school acts as the primary driver through various programs such as integrating preventive material into the curriculum, conducting regular counseling sessions with the National Narcotics Board (BNN), and implementing a student participation-based early detection system named "Sahabat Sehat" (Healthy Friends). On the other hand, parents provided tangible contributions despite facing constraints of time and economy, mainly through preventive dialogue at home and support for school policies, utilizing WhatsApp groups as an efficient communication medium. Analysis using Role Theory indicates that the success of this synergy is underpinned by the clarity and alignment of roles between the school and parents. In conclusion, this adaptive, context-specific bottom-up synergy model proves effective for implementation in communities with low socio-economic status.